An approach to provide efficient choices to a household consumer - Santos, Ricardo (2019)
In this work, it will be presented an approach, applied to an energy efficiency problema in buildings, which allows the decision-agent (consumer) to perform a set of efficient choices, suitable to its needs, reducing therefore, the building overall energy consumption during the equipment lifecycle period (usage phase). The approach will use Evolutionary Algorithms (EA), combined with Multicriteria analysis. The quality of EA solutions will be evaluated through the comparison, with the ones, obtained from Simplex method. The EA robustness to the change of its parameters, will also be evaluated, as well as the influence of the objective function on its behavior. The approach can provide the consumer with several and different efficient solutions, with less time than Simplex. I tis also possible to improve the obtained solutions, by choosing adequately the EA`s control parameters, as well the problema formulation.